2016
DOI: 10.1007/s00360-016-0959-3
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic flexibility of energetics in acclimated Siberian hamsters has a narrower scope in winter than in summer

Abstract: As photoperiod shortens with the approach of winter, small mammals should reduce their energy expenditure to survive periods of food limitation. However, within seasons, animals should balance their energy budgets as abiotic conditions change, sometimes unpredictably; cold spells should increase heat production, while warm spells should do the opposite. Therefore, we addressed specific questions about the possible interactions between seasonal acclimatization and the intra-seasonal phenotypic flexibility of me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 97 publications
(151 reference statements)
1
26
1
Order By: Relevance
“…Such phenotypic flexibility may be crucial in response to changes in environmental conditions, especially in the face of present and predicted climate change (present study; Cooper et al 2020b;Noakes and McKechnie 2019;Noakes et al 2016;Oswald et al 2018;Tieleman et al 2002bTieleman et al , 2002aTieleman 2000, 2002). Possibly, this phenotypic flexibility may also undergo seasonal changes as it was shown in mammals (Boratyński et al 2016a(Boratyński et al , 2017b. Also, since thermal history may affect flexibility of energy metabolism (Barcelo et al 2009), we cannot exclude that acclimation to high T a 's in summer may additionally facilitate flexible adjustments of thermoregulatory traits.…”
Section: Discussionmentioning
confidence: 90%
“…Such phenotypic flexibility may be crucial in response to changes in environmental conditions, especially in the face of present and predicted climate change (present study; Cooper et al 2020b;Noakes and McKechnie 2019;Noakes et al 2016;Oswald et al 2018;Tieleman et al 2002bTieleman et al , 2002aTieleman 2000, 2002). Possibly, this phenotypic flexibility may also undergo seasonal changes as it was shown in mammals (Boratyński et al 2016a(Boratyński et al , 2017b. Also, since thermal history may affect flexibility of energy metabolism (Barcelo et al 2009), we cannot exclude that acclimation to high T a 's in summer may additionally facilitate flexible adjustments of thermoregulatory traits.…”
Section: Discussionmentioning
confidence: 90%
“…Being a small alpine mammal that does not hibernate, the American pika may be especially dependent on a fine‐tuned metabolic rate, given that smaller animals would be disproportionately affected by low temperatures (Moyer‐Horner et al., ). As a case in point, Boratyński, Jefimow, and Wojciechowski () found that both the basal metabolic rate and nonshivering thermogenesis in Siberian hamsters were highly plastic during the summer months to meet local thermal conditions. If such patterns generalize to the current study, the elevational pattern of GC reported here may represent the metabolic plasticity of pikas to local thermal conditions.…”
Section: Discussionmentioning
confidence: 99%
“…For examples, guppies ( Poecilia reticulata ) change their RMR in response to predators (Handelsman et al., ), mouse ( Mus musculus ) RMR fluctuates over the course of pregnancy (Speakman & McQueenie, ), and generally, birds’ RMR changes in response to cool, seasonal temperatures (McKechnie, ). In addition, experimental studies in hamsters ( Phodopus sungorus ) have demonstrated marked differences in metabolic rate in response to short‐term differences in ambient temperature (Boratyński, Jefimow, & Wojciechowski, , ). Thus, there is ample evidence suggesting that plasticity in metabolic rate allows organism to quickly adjust to short‐term changes in the environment.…”
Section: Introductionmentioning
confidence: 99%